O poeta é sempre rapsodo: a presença da música na obra de Mário de Andrade - FREITAS, Danilo Mercês (Universidade Federal do Pará, 2017)
The literature on Mário de Andrade walks together with the music because this author privilege his sonorous choices and also use the structure of musical genders as a way of poetic creation. Besides, it's necessary to consider the constant revision whose the writer does is his work, mainly on the systematization of the modernist moviment and the comprehesion of the brazilian people identity. Thus, the present work tries to comprehend how music influences Mário's writing on three works among them all: Pauliceia Desvairada (1922), Clã do Jabuti (1927) and Lira Paulistana (1945). Many changes will be happenning on his musical choises, on the first one, the author is more interested on proclaim and divulge the modernist moviment, the art of sounds is used to consolidate the new avant-garde sources as well as to free the artist from the poetic traditionalism; on the second work chose, the author explore songs and commons brazilian popular musical genders to legitimate them on the universe of classical music, this way it contributes to the definition of the brazilian culture and identity; on Lira Paulistana the author used portuguese medieval chants and changed it in order to sing the city of São Paulo and the man whom lives there on the early XIX century. It hopes this study could contibute on researchs about the modernist writer where the comprehension of the music on the poetic writing of Mário de Andrade can promote an deeper understanding on his works. The methodology used was to work closely in the poetry and essays of Mário de Andrade, searching in this works the necessary instruments to the analysis. The present work used studies of PIVA (1990), CORREIA (2010), SOUZA (2006) and critic works written by Mário de Andrade.